2‐Quinolyl Benzodiazaborine: A Tunable Platform for Aggregation‐Induced Emission Luminogens via Formation of Dimeric Borate Crystals with Acid Additives. Issue 3 (30th December 2021) - Shimo, Shunsuke; Nakamura, Takumu; Takahashi, Kohei; Toriumi, Naoyuki; Iwasawa, Nobuharu
Abstract: 2‐Quinolyl benzodiazaborine (DAB) was synthesized and its conversion to a borate species was investigated. Addition of carboxylic acids and hydrogen fluoride led to facile formation of a stable borate derivative, whose structure was unambiguously characterized by single crystal X‐ray diffraction analysis. The borates show intense aggregation‐induced emission (AIE) in crystals, which is thought to be derived from a rigid dimeric structure with intermolecular hydrogen bonding. Abstract : Benzodiazaborines containing a quinoline moiety were converted into the corresponding borate complexes which exhibited efficient aggregation‐induced emission (AIE) upon addition of acids. The X‐ray diffraction analysis of the borates indicated that the dimeric structures with intermolecular hydrogen bonding and reduced intermolecular π‐π interactions are responsible for the AIE properties.